An optimized ionizable cationic lipid for brain tumor-targeted siRNA delivery and glioblastoma immunotherapy. (August 2022) - Liu, Shuhan; Liu, Ji; Li, Haisong; Mao, Kuirong; Wang, Haorui; Meng, Xiandi; Wang, Jialiang; Wu, Chenxi; Chen, Hongmei; Wang, Xin; Cong, Xiuxiu; Hou, Yue; et al.
Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor with a high mortality rate. Immunotherapy has achieved promising clinical results in multiple cancers, but shows unsatisfactory outcome in GBM patients, and poor drug delivery across the blood-brain barrier (BBB) is believed to be one of the main limitations that hinder the therapeutic efficacy of drugs. Herein, a new cationic lipid nanoparticle (LNP) that can efficiently deliver siRNA across BBB and target mouse brain is prepared for modulating the tumor microenvironment for GBM immunotherapy. By designing and screening cationic LNPs with different ionizable amine headgroups, a lipid (named as BAMPA-O16B) is identified with an optimal acid dissociation constant (p K a) that significantly enhances the cellular uptake and endosomal escape of siRNA lipoplex in mouse GBM cells. Importantly, BAMPA-O16B/siRNA lipoplex is highly effective to deliver siRNA against CD47 and PD-L1 across the BBB into cranial GBM in mice, and downregulate target gene expression in the tumor, resulting in synergistically activating a T cell-dependent antitumor immunity in orthotopic GBM. Collectively, this study offers an effective strategy for brain targeted siRNA delivery and gene silencing by optimizing the physicochemical property of LNPs. The effectiveness of modulating immune environment of GBM could further be expanded for potential treatment of other brain tumors. Graphical abstract: To efficiently deliver siRNA across BBB for modulating the tumor microenvironment of GBM, a leading lipid (BAMPA-O16B) is identified as an efficient carrier to deliver siRNAs into intracranial tumor tissues. The BAMPA-O16B/siRNA lipoplex induces CD47 and PD-L1 simultaneous silencing and activates antitumor immunity, highlighting the great potential of using brain-targeted liposomal siRNA delivery for the immunotherapy of GBM and other brain tumors. Image 1